Sepsis in Patients With Large Vessel Occlusion Stroke–Clinical Characteristics and Outcome - Stösser, Sebastian; Isakeit, Julia; Bode, Felix J.; Bode, Christian; Petzold, Gabor C. (Frontiers in Neurology, 2022)
Background: Infections are an important complication after stroke and negatively affect clinical outcome. While pneumonia and urinary tract infections are well recognized after stroke, the incidence and consequences of sepsis remain unclear. The aim of this study was to evaluate the frequency and characteristics of sepsis in patients undergoing endovascular therapy for large vessel occlusion stroke, and its association with clinical outcome. Methods: We analyzed a cohort of patients who underwent endovascular therapy at a single center between 2016 and 2020. The diagnosis and timing of infections and Sequential Organ Failure Assessment scores were evaluated retrospectively to identify patients with sepsis. Patients with sepsis were compared to controls regarding clinical characteristics and outcome. Results: Fifty-four of 406 patients (13.3%) were found to have sepsis. The median onset of sepsis was two days after admission. The majority of cases (85.2%) was caused by pneumonia. At three months, 72.5% of patients with sepsis were bedridden or dead compared to 25.7% and 42.7% of controls and patients with an infection without sepsis, respectively. The adjusted odds ratio (95% confidence interval) for a poor outcome was 5.4 (1.6-17.6) for patients with sepsis versus controls, and 2.0 (0.8-5.2) for patients with sepsis versus patients with an infection without sepsis. Conclusions: Sepsis is a frequent complication after large vessel occlusion stroke, and may be associated with a poor clinical outcome. More studies are needed to determine specific risk factors and measures to early recognize and reduce the possibly negative impact of sepsis on outcome after stroke.